2006
DOI: 10.1038/sj.onc.1209668
|View full text |Cite
|
Sign up to set email alerts
|

Bak functionally complements for loss of Bax during p14ARF-induced mitochondrial apoptosis in human cancer cells

Abstract: In contrast to the initial notion that the biological activity of p14 ARF strictly depends on a functional mdm-2/p53 signaling axis, we recently demonstrated that p14 ARF mediates apoptosis in a p53/Bax-independent manner. Here, we show that p14 ARF induces breakdown of the mitochondrial membrane potential and cytochrome c release before triggering caspase-9-and caspase-3/7-like activities in p53/Bax-deficient DU145 prostate cancer cells expressing wild-type Bak. Re-expression of Bax in these cells failed to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 47 publications
3
38
0
Order By: Relevance
“…This suggests that BetA-induced apoptosis is activated in a Bax/Bak-independent, but mitochondriadependent fashion. To rule out the possibility that these findings are selective for MEFs we also obtained HCT116 colon cancer cells that were made deficient for both Bax and Bak [27,28]. Similar to the MEFs, we observed that BetA-induced apoptosis was readily induced in cells lacking Bax and Bak (Fig.…”
Section: Beta-induced Apoptosis Depends On the Apoptosomementioning
confidence: 77%
“…This suggests that BetA-induced apoptosis is activated in a Bax/Bak-independent, but mitochondriadependent fashion. To rule out the possibility that these findings are selective for MEFs we also obtained HCT116 colon cancer cells that were made deficient for both Bax and Bak [27,28]. Similar to the MEFs, we observed that BetA-induced apoptosis was readily induced in cells lacking Bax and Bak (Fig.…”
Section: Beta-induced Apoptosis Depends On the Apoptosomementioning
confidence: 77%
“…1D). Oligomerization of proapoptotic proteins belonging to the Bcl-2 family, such as Bax and Bak, is responsible for formation of PTPs in mitochondria (7,20,22,25,37,39,40,50). These PTPs release cytochrome c, AIF, Smac and EndoG from the intermembrane space of mitochondria, leading to apoptosis of the cells (2,11,23,43,48).…”
Section: Discussionmentioning
confidence: 99%
“…HCT116/wt, HCT116/p53 À/À , HCT116/bax À/À (kindly provided by B Vogelstein), 31 and HCT116 cells stably expressing Bak siRNA (HCT116/bak knockdown and HCT116/bax À/À /bak knockdown ) 32 were maintained in McCoy's 5A medium, supplemented with 10% heat-inactivated fetal calf serum, 10 mM glutamine and antibiotics (100 U/ml penicillin, 0.1 mg/ml streptomycin) (PAA Laboratories, Linz, Austria). HeLa cells were cultured in RPMI-1640 (PAA Laboratories) with identical supplements.…”
Section: Methodsmentioning
confidence: 99%